TFAP2A upregulates FAM83A to suppress ferroptosis and diminish cisplatin sensitivity in non-small cell lung cancer - Qi Sun; Weifeng Qu; Ye Wang; Kejia Yang; Yuan Weng (Cell Division)
Abstract Background FAM83A plays a significant role in the development of non-small cell lung cancer (NSCLC). This study elucidated the biological role of FAM83A in ferroptosis and cisplatin (DDP) sensitivity in NSCLC cells. Methods The expression patterns of FAM83A and TFAP2A were analyzed by bioinformatic analysis. mRNA and protein levels were detected by quantitative PCR, immunoblotting, and immunohistochemistry, respectively. Cell invasion, migration, and viability were assessed by transwell, wound healing, CCK-8 assays, respectively. Cell ferroptosis was evaluated by measuring the levels of ROS, Fe2+, MDA, GSH, and SOD. Chromatin immunoprecipitation (ChIP) and luciferase assays were used to confirm the relationship between TFAP2A and the FAM83A promoter. Xenograft models were generated to evaluate the role of TFAP2A in vivo. Results FAM83A and TFAP2A levels were upregulated in human NSCLC. FAM83A inhibition decreased NSCLC cell growth, motility, and invasiveness, while inducing ferroptosis and enhancing DDP sensitivity. Mechanistically, TFAP2A regulated FAM83A transcription in NSCLC cells. TFAP2A depletion suppressed the malignant behaviors of NSCLC cells and augmented their sensitivity to ferroptosis and DDP, and these effects were reversed by the upregulation of FAM83A. Additionally, TFAP2A depletion decreased the growth of A549 subcutaneous xenografts in vivo. Moreover, the TFAP2A/FAM83A cascade regulated the activation of the PI3K/AKT and Wnt/β-catenin pathways. Conclusion Our study demonstrates that the novel TFAP2A/FAM83A cascade modulates ferroptosis and drug sensitivity in NSCLC.